Investigating and Supporting the Chemistry-Specific and Academic Literacy of Introductory Chemistry Students - (:unkn) unknown (My University, 2024)
In chemical education, it is well-known that novices struggle to comprehend and synthesize the large volume of abstract material presented in their chemistry classes. This is in part due to the specific linguistic conventions of chemistry and other science text and the considerable cognitive labor that learners must do to construct their own cohesive knowledge of the subject from the materials presented to them. Students who do not develop the chemistry-specific disciplinary literacy needed to interpret chemistry text and synthesize its contents may be at risk of failing or withdrawing from chemistry classes. Such students can benefit from support to enhance the comprehension and learning skills needed to succeed in chemistry classes. While both linked courses and discipline-specific literacy supports have shown promise in supporting chemistry students’ success, a dedicated chemistry literacy support course has not been described in the literature. This work describes efforts to understand how Introductory Chemistry students at the University of Wisconsin–Milwaukee navigate the comprehension tasks of chemistry, and to create a support course to help students develop their chemistry-specific literacy skills. A mixed-methods approach involving surveys, interviews, and assessments was used to better understand how Introductory Chemistry students approach and understand chemistry texts, and a one-credit chemistry literacy support course was collaboratively developed and co-taught by chemical education researchers and experts in college reading pedagogy; a mixed-methods approach that combined qualitative interview data with quantitative data from Introductory Chemistry was also used to evaluate the linked course. Conclusions from this work illustrate the specific challenges experienced by novices in interpreting chemistry text and suggest ways in which instructors can support their students in developing the skills to interpret and synthesize chemistry content.
Keywords: college reading; disciplinary literacy; introductory chemistry students